Bacterial populations in different parts of domestic drinking water systems are distinct and adapted to the given ambient temperatures - Meyer, Benjamin; Pannekens, Mark; Soares, André R.; Timmermann, Lara; Probst, Alexander J.; Hippelein, Martin; Bendinger, Bernd; Nocker, Andreas (Frontiers in Water, 2023)
Drinking water enters buildings with a given microbiological community composition. Within premise plumbing systems, the drinking water is subject to very different conditions and temperatures. Whereas part of the water stays cold, another part is heated to provide hot water. In this study, drinking water samples were taken at different locations in four buildings that had central heating circles and that were equipped with ultrafiltration modules. The latter were intended to keep bacterial numbers low. When studying the increase in bacterial concentrations in these water samples using regrowth tests at different incubation temperatures, a temperature-dependence could be observed. Bacteria in cold water samples propagated best when incubated at 22°C, but often poorly at 36°C and not at all at 50°C. Bacteria in hot water samples showed the reverse behaviour and grew best when incubated at 50°C, whereas growth at 22°C was poor or associated with a long growth lag. Water samples from distal taps in periphery locations used for retrieving both cold and hot water showed intermediate growth behaviours. Results suggest the existence of different temperature-adapted bacterial populations within domestic drinking water systems. The finding was supported by sequence data revealing distinct differences in the microbiomes between cold and hot water samples. Abundant bacterial groups in hot water included Deinococci, Kryptonia, Ignavibacteria, Nitrospiria, Gemmatimonadetes and different genera of Gammaproteobacteria. Stagnation of hot water at 50°C, 55°C or 60°C furthermore shaped the microbiome in different ways indicating that small temperature differences can have a substantial impact on the bacterial communities.